An Exploration of Smoking Patterns Among People with Serious Mental Illness Attending an Outpatient Clinic in Qatar - Monica Zolezzi (10115698) (2022)
Background Studies have shown that tobacco use is exceptionally high in people affected with serious mental illness (SMI). Many countries worldwide have observed a decrease in the prevalence of tobacco smoking; however, the smoking rates among people with SMI have declined much less than in those without mental illness. To date, no nationally representative data have examined the smoking patterns or the sociocultural factors that influence smoking among SMI people in Qatar. Methods A retrospective medical chart review was conducted to collect patient demographics, psychiatric and medical comorbidities, medications, the most recently documented smoking status and if on tobacco cessation treatment. A descriptive and inferential analysis of the data was performed. Results: Of 346 patients included in the cohort, 196 (56.6%) had their smoking status documented, of which 72 (36.7%) were “currently smoking.” Significantly more males than females were “current smokers” (62.9% versus 15.0%, respectively, p < 0.001). Significantly more patients with psychotic disorders than those with any other SMI were “current smokers”, and this difference was statistically significant (p = 0.006). Positive and significant associations with current smoking were found for the male gender, psychotic disorders, and high levels (≥6.2 mmol/L) of total cholesterol. Only 12 (16.7%) of current smokers were receiving smoking cessation treatment. Conclusion More than half of a sample of people with SMI attending outpatient psychiatric services in Qatar had documented smoking status. Still, only a few current smokers were on smoking cessation treatment. Efforts are needed to implement smoking cessation strategies in this population. Other Information Published in: Neuropsychiatric Disease and Treatment License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.2147/NDT.S385970